E Buddy's Impact on Local Governance in Indonesia through Transforming Document Management - Hanifah, Ayum; Rodiyah, Isnaini (Indonesian Journal of Cultural and Community Development, 2024)
General Background: The advent of electronic document management systems has revolutionized administrative processes in local governance, emphasizing the need for effective implementation strategies. Specific Background: In Indonesia, the Electronic Official Document Arrangement through the E Buddy application has been introduced to enhance the efficiency of village governance, particularly in Panggreh Village, Jabon Sub-district, Sidoarjo Regency. Knowledge Gap: However, challenges remain regarding the consistency and effectiveness of E Buddy's usage among village officials, particularly concerning communication, resource allocation, and bureaucratic structures. Aims: This study aims to analyze and describe the implementation of the E Buddy application in Panggreh Village using a qualitative descriptive method, focusing on the indicators proposed by George Edward III: communication, resources, disposition, and bureaucratic structure. Results: The findings indicate that while E Buddy has been implemented, issues persist, such as inconsistent usage of the application for official document transmission and inadequate technical guidance. Furthermore, some officials struggle with the application’s functionalities, and insufficient resources hinder optimal performance. The study also highlights the need for dedicated personnel, improved evaluation methods, and the establishment of incentives to motivate village officials in utilizing E Buddy effectively. Novelty: This research contributes to the understanding of the practical implications of electronic document management systems in local governance, offering insights into the barriers faced by village officials in Indonesia. Implications: The results underscore the necessity for continuous training, resource upgrades, and structural reforms to enhance the efficacy of the E Buddy application and improve service delivery in rural governance. Highlights: Communication Issues: WhatsApp used instead of E Buddy for documents. Resource Deficiencies: Officials lack skills in using E Buddy effectively. Regulatory Compliance: Structure follows regulations, but support needs improvement. Keywords: E Buddy, Electronic Document Management, Implementation, Local Governance, Sidoarjo Regency